Synthesis and Study of Magnetic and Magneto - Transport Properties of some Topological Insulators - Singh, Abhishek (IIT(BHU), Varanasi, 2018)
Abstract is available in the attachment
This Thesis submitted by PhD Scholar IIT(BHU), Varanasi and supervised by Prof. Sandip Chatterjee.
Keywords: Synthesis; Magnetic; Insulators